1991
DOI: 10.1182/blood.v78.7.1652.1652
|View full text |Cite
|
Sign up to set email alerts
|

P53 gene mutations in acute myeloid leukemia with 17p monosomy

Abstract: We looked for mutations of exons 5 to 8 of the P53 gene in 10 patients with acute myeloid leukemia (AML) and 17p monosomy, and 36 patients with AML and no cytogenetic abnormalities of 17p. DNA was analyzed by polymerase chain reaction, single-strand conformation polymorphism analysis, and nucleotide sequencing. Four of the 10 patients with 17p monosomy showed point mutation, single-nucleotide deletion, or insertion in exons 7 or 8. By contrast, only 1 of the 36 patients with AML and no cytogenetic abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Haferlach et al (27) reported that TP53 mutations were strongly associated with the complex karyotype in AML, but the association with dysplastic morphology was not evaluated; however, our results indicate that this genotype is closely associated with dysplastic morphology regardless of the history of MDS. It has been reported that TP53 mutation is associated with loss of chromosome band 17p13, where the TP53 gene is located (9,28). Deletion of 17p, which occurred by unbalanced translocation between chromosome 17p and another chromosome, monosomy 17 or i (17), is reportedly observed in 3-4% of AML and MDS and 10-15% of therapy-related MDS or AML (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Haferlach et al (27) reported that TP53 mutations were strongly associated with the complex karyotype in AML, but the association with dysplastic morphology was not evaluated; however, our results indicate that this genotype is closely associated with dysplastic morphology regardless of the history of MDS. It has been reported that TP53 mutation is associated with loss of chromosome band 17p13, where the TP53 gene is located (9,28). Deletion of 17p, which occurred by unbalanced translocation between chromosome 17p and another chromosome, monosomy 17 or i (17), is reportedly observed in 3-4% of AML and MDS and 10-15% of therapy-related MDS or AML (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Seven of the 11 TP53 mutated cases showed overlap mutations: two was overlapped with MLL-PTD and each one with NPM1, C ⁄ EBPA, AML1, cKIT, and FLT3 ⁄ ITD mutations. Cytogenetic analysis revealed that 10 TP53 mutated cases had abnormal karyotypes: eight were complex karyotype, five of which had a deleted chromosome 17, and each one was 46XY, del(5q) and 46XY, t(8;21), del (9). Importantly, one case with TP53 mutation and the karyotype 46XY, del(5q) harbored FLT3 ⁄ ITD, and one case with TP53 mutation and the karyotype 46XY, t(8;21), del(9) harbored cKIT mutation.…”
Section: Overlap Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In AML, 17p mutation occurs in about 3-8% of cases and contributes to disease progression and development of resistance to drug therapy. p53 mutation is associated with advanced disease and short survival (Aas et al, 1996;Lai et al, 1995;Fenaux et al, 1991;Wattel et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In haematological malignancies, p53 mutations are less frequent than in solid tumours but are an important factor for response to chemotherapy and prognosis (Harris & Hollstein, 1993). In AML, p53 mutations occur in 5-8% (Fenaux et al, 1991;Stirewalt et al, 2001;Hu et al, 1992;Trecca et al, 1994). Aberration in the p53 gene is most frequently found in patients with secondary AML and complex karyotype.…”
mentioning
confidence: 99%